Historical glimpses of a number of historians and orientalists as they express their love for Iraq and Baghdad throughout history - Aziz, Sadiq Abdul Muttalib (Al-Adab Journal, 2021)
I hope that I have succeeded in transmitting the testimonies of some foreign writers and orientalists about Baghdad, which remained resistant to the colonialists and occupiers in all their forms and nationalities, and resisted and confronted all kinds of destruction and sabotage, and preserved its bright face throughout the ages to be the capital of Arab culture, because its roots and cultural and civilizational legacy extend in the subsoil of the earth. And as the French orientalist “Andre Clough” said, “The earth rotates according to the time of Baghdad… These orientalists and writers I met and spoke to me a lot about Baghdad in addition to their writings, which I transferred a small part of due to lack of time. And the role of translation in the transfer of this legacy and cross-fertilization with civilizations.